Genome sequence of an aichivirus detected in a common pipistrelle bat (Pipistrellus pipistrellus) ... - Diakoudi, Georgia; Jamnikar-Ciglenečki, Urška; Lanave, Gianvito; Lelli, Davide; Martella, Vito; Kuhar, Urška (Zenodo, 2020)
(Uploaded by Plazi for the Bat Literature Project) The family Picornaviridae includes important human and animal pathogens that are associated with a wide range of diseases and, in some cases, have zoonotic potential. During epidemiological surveillance of bats, we identified, by next-generation sequencing (NGS) techniques, the presence of picornavirus RNA in a common pipistrelle bat (Pipistrellus pipistrellus). By coupling NGS, primer-walking strategies, and sequence-independent protocols to obtain the sequences of the 5′ and 3′ termini, we reconstructed the genome sequence of picornavirus strain ITA/2017/189/18-155. The genome of the bat picornavirus is 8.2 kb in length and encodes a polyprotein of 2462 amino acids. A comparison of polyprotein sequences revealed that this virus is distantly related (65.1% and 70.9% sequence identity at the nucleotide and amino acid level, respectively) to a bat aichivirus identified in 2010. Phylogenetic analysis showed that this picornavirus clustered closely with members ...